ANÁLISE DO TRIPLE BOTTOM LINE EM UMA CORPORAÇÃO MULTINACIONAL NO BRASIL - Vione, Cristiane Ivete Bugs; Da Rosa, Caroline; Brizolla, aria Margarete Baccin; Baggio, Daniel Knebel (Salão do Conhecimento, 2019)
Responsabilidade Social Empresarial